ENHANCING SME DIGITAL MARKETING THROUGH A WEB-BASED E-COMMERCE SYSTEM WITH AUTOMATED WHATSAPP ORDERING - Nungsiyati Nungsiyati; Hafid Hafid; Vina Putri Agustiyani (YHMM PUBLISHING, 2026)
The rapid advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing strategies through e-commerce platforms to improve competitiveness and business performance. However, many MSMEs still face challenges in managing online transactions, customer communication, and digital promotion effectively. This study aims to implement a web-based mobile e-commerce system integrated with automated WhatsApp ordering features for UMKM Barokah to support digital marketing activities and improve customer service quality. The research employed a quantitative approach using observation, interviews, system implementation, and questionnaire distribution to 76 customers during the July–September 2025 period. The system was developed using a web mobile platform integrated with WhatsApp communication features to facilitate direct interaction between customers and sellers. Quantitative testing results showed that the system achieved a very good acceptance rate, with overall customer satisfaction reaching 89.1%. The perceived ease of use obtained a score of 90.2%, interface appearance 87.4%, interactive communication 89.3%, and transaction speed through automated WhatsApp ordering 92.1%. The findings indicate that integrating e-commerce with WhatsApp automation significantly improves digital marketing effectiveness, customer engagement, transaction efficiency, and repurchase intention. Furthermore, the system successfully reduces manual transaction errors and enhances operational efficiency for MSMEs. Therefore, the proposed system can serve as an innovative digital transformation model for MSMEs in strengthening online marketing strategies and improving customer relationship management in the digital business era.